EDUCATION ABOUT BREAST CANCER IN THE COMMUNITY AT NGLUYU HEALTH CENTER, NGANJUK - Mastutik, Gondo; Fauziah, Dyah; Rahaju, Anny Setijo; Rahniayu, Alphania; Ridholia; Kurniasari, Nila; Kusumastuti, Etty Hari; Ilmiah, Khafidhotul (Universitas Airlangga, 2024)
Breast cancer is the most common cancer found in the world and this cancer is the second cause of death due to cancer after lung cancer in Indonesia. This high mortality rate can be prevented by carrying out early detection. However, this is still not done well, especially in communities living in remote areas with low to medium economic and educational levels. The aim is to convey knowledge about breast cancer and training in the self-examination of the breast. It was held on Tuesday, 12 September 2023 at the Ngluyu Community Health Center, Nganjuk, from 07.00 to 14.00 WIB and was attended by 111 people. Data on breast cancer risk factors was collected through questionnaires. There were 96 participants who filled out the questionnaire, aged between 22-63 years. Risk factors data showed that 3.13% did not have children, 15.63% breastfed children less than 6 months, 5.21% were exposed to X-rays more than once a year; 1.04% had breast tumors, and 4.17% had family members suffering from cancer. In addition, 89.58% were over 25 years old and 42.71% had doing self-examination of breast. There was an increase in public understanding at the Ngluyu Community Health Center from 77.70% to 84.12%, namely an increase of 6.42%. This can increase public understanding about breast cancer and procedures to self-examination of breast and contribute in early detection of breast cancer as well as reducing the incidence of breast cancer. The results of this counseling can be used as recommendations by health centers in the Nganjuk district area.